Rathke's Cleft Cyst as Origin of a Pediatric Papillary Craniopharyngioma - Schlaffer, Sven-Martin; Buchfelder, Michael; Stoehr, Robert; Buslei, Rolf; Hölsken, Annett (Frontiers in Genetics, 2018)
A 6-year old male patient presented with an intra and suprasellar cystic lesion accompanied with impairment of the hypothalamic-pituitary axis and partial hypopituitarism. The most likely cause of sellar lesions in this age group are adamantinomatous craniopharyngioma (adaCP) or Rathke`s cleft cysts (RCCs). AdaCP are characterized by CTNNB1 mutations accompanied with aberrant nuclear beta-catenin expression. RCC show neither nuclear beta-catenin expression nor BRAF mutation. The latter is a hallmark of papillary craniopharyngiomas (papCP) that exhibit remarkable histological similarity with metaplasia of RCC. Diagnosis of the patient was elucidated by CTNNB1 and BRAF mutation screening, utilizing different approaches, as well as histological examination of markers e.g. beta-catenin, claudin-1, EpCAM and the mutated BRAFV600E protein, which are known to be differentially expressed in sellar lesions. The case presented reveals extraordinary aspects for two reasons. Firstly, the lesion appeared clinically, on MRI, intraoperatively and histologically as RCC with prominent squamous metaplasia, but showing an expression pattern of markers also found in papCP, whilst exhibiting a hitherto undescribed BRAFV600E mutation. This important result documents a supposable transition of RCC metaplasia into a papillary craniopharyngioma (papCP). Secondly, this intriguing case shows unexpectedly that although papCP usually occurs almost exclusively in adults, it can also arise in childhood.